The Long Program for Ethics in Ethnobiology - Fowler, Cynthia T.; Herron, Scott (Ethnobiology Letters, 2018)
Ethics is a core interest of practicing ethnobiologists and a function of healthy relationships between individuals, cultures, researchers, and the foci of study. Changing times and cultural identities require clear reflections among scientists and responsive interactions with the individuals and cultures who work with ethnobiologists. This Ethnobiology Letters special issue, “Ethics in Ethnobiology,” explores the diverse ways in which intentional conversations about ethics guide us as we encounter unforeseen circumstances and witness changing values in ourselves as well as our collaborators. Moreover, by integrating the ethics of diverse interlocutors into their own research endeavors, these authors illustrate how ethnobiologists listen deeply to the values of their research collaborators.